A performance of embedding process for text steganography method - Osman, Baharudin; Din, Roshidi; Tuan Muda, Tuan Zalizam; Omar, Mohd Nizam (2013)
One of the main aspects on embedding process of any text steganography methods is the capacity text.It is because a better embedding ratio and saving space offers; a more text can be hidden. This paper tries to evaluate several format based techniques of text steganography based on their embedding ratio and saving space capacity.Thus, main objective of this paper is to analyze the performance of text steganography methods which are CALP, Vertical based and Quadruple methods based on these two capacity factors.It has been identified that vertical based method give a good effort performance compared to CALP and Quadruple based method.In future, a robustness of text steganography methods should be considered as a next effort in order to find a strength capability on text steganography.